Las trabajadoras sociales en la década de 1930. Asistir a los pobres y servir al Estado - Lorenzo Río, María Dolores (El Colegio de México, A.C., 2018)
Studying the integration of new professions in the welfare bureaucracy is one of the best ways to explain the modernization of public services. In this article, we examine how social workers were involved into the Beneficencia Pública del Distrito Federal. We propose that, along the decade of 1930's, these employees fulfilled various tasks and strenuous working days in exchange for low wages. Despite this conditions, they gain a place as employees of public social services. Also in this process, schoolar formation, the recognition of the government and the feminization of their activities, institutionalized the profession of social work in Mexico. In the text, it is shown that the transformation of the state does not arise only from the enunciation of an administrative, secular and progressive reform in favor of social rights, because the hard work of people is necessary to archive it.